Advanced Practice Providers in the Field: Implementation of the Los Angeles Fire Department Advanced Provider Response Unit. (2nd September 2020) - Sanko, Stephen; Kashani, Saman; Ito, Terrance; Guggenheim, Aaron; Fei, Shangnon; Eckstein, Marc
Abstract: Background: To address the growing number of low-acuity patients in the 911-EMS system, the Los Angeles Fire Department (LAFD) launched a pilot program placing an Advanced Provider Response Unit (APRU) in the field so that a prehospital nurse practitioner (NP) could offer patients treatment/release on scene, alternative destination transport, and linkage with social services. Objective: To describe the initial 18-month experience implementing this new APRU. Methods: This is a retrospective, descriptive review of all APRU-attended patients from January 2016 to June 2017. The APRU was an ambulance staffed by an NP and a firefighter/paramedic, equipped with basic point-of-care testing capability, and linked to incidents by either being summoned by on-scene first responders or by monitoring EMS radio traffic. Descriptive statistics were used and outcome measures included counts of clients attended, treat/release rates, impact on total time in service for other LAFD resources, patient need for subsequent re-use of 911 and self-reported experience of care. Results: During its first 18 months in service, the APRU attended 812 patients, including 792 911-patient incidents. 400 of these 911-patients (50.5%) were treated and released on scene or medically cleared and transported to an alternative site for specialty care. This included 76 patients with primary psychiatric complaints who were medically-cleared and transported directly to a mental health urgent care center. An additional 18 high utilizers of 911 were attended by the APRU and connected with a social work organization, and 12 of 18 (66.7%) decreased their use of EMS in the 90-days following APRU evaluation and referral. Of the 400 911-patients that did not go to the emergency department (ED), 26 (6.5%) re-contacted 911 within 3 days: all were transported to the ED with normal vital signs and without prehospital intervention, and all were ultimately discharged home from the ED. As a result of APRU intervention, 458 other LAFD field resources were quickly placed back in service and made available for the next time-critical call. Conclusions: Advanced practice providers such as nurse practitioners can be incorporated into the prehospital setting to address a growing subset of 911-patients whose needs can be met outside of the ED.